Insect Quarantine Status in Association with Imported Commodities from Timor Leste Passed through Agricultural Quarantine Ware of Mota'ain-District of Belu - Astuti Handayani; Fransiscus Xaverius Wagiman; Siwi Indarti; Suputa Suputa (Universitas Gadjah Mada, 2019)
Timor Leste is one of the exporting countries of agricultural products to Indonesia via the Mota'ain-Belu Regency cross-border. Imported commodities from the country may constitute those which are possible as Pest Quarantine (PQ) carrier media into Indonesia. The status of insect quarantine associated with imported commodities has been studied. Sampling of imported commodities both as open trucks shipments and toted passenger bags are done based on the Agricultural Quarantine Product Sampling Guidelines using the Non-Statistic method (convenience). Samples of commodities in the form seeds or grains were taken as much as 250 grams, while other forms were taken as much as 500 grams. For this study, 40 sample units were taken from seven commodities. The commodity samples were stored for 30 days at the laboratory of Agricultural Quarantine office in Kupang, as most life cycle of postharvest insects ranges from 3 to 5 weeks. Specimens of the infecting insects were identified and their quarantine status were determined. The results showed that there were eight different insects species found in association with six kinds of commodities, while in one sample of rice no insect was found. In robusta coffee the insects found were Necrobia rufipes, Hypothenemus hampei, Cryptolestes ferrugineus, and Pyralis manihotalis. In arabica coffee we found H. hampei, and C. ferrugineus. In copra, there were N. rufipes, and Carpophilus dimidiatus. In red beans, there were Callosobruchus chinensis. In mixed red beans, peanuts, and soybeans C. chinensis, C. dimidiatus, and Sitophilus oryzae were found, and in the candlenut there were Oryzaephylus surrinamensis, and C. dimidiatus. All of the insects found in the examined commodities had plant pests status. The highest number of insects associated with the examined commodities from 40 sample units were H. hampei insects found in arabica coffee, which were 62.3 individuals. N. rufipes insects in copra commodity samples appeared on the 25th day after sampling, which meant they were the fastest among other insects.